EXPLORING ESP NEEDS OF UNDERGRADUATE NURSING STUDENTS IN A UNIVERSITY IN INDONESIA - Nurakhir, Asih (Advances in Social Sciences Research Journal, 2018)
The purpose of this study was to investigate the English for specific Purposes (ESP) needs of nursing students in a university in Semarang, Indonesia. This study employed a descriptive qualitative design and involved a total of 116 undergraduate students recruited using purposive sampling. A self-administered questionnaire adopted from from Chia, Johnson, Chia, & Olive (1999) was utilized. To meet the purpose of the study, some necessary adjustments were made to the questionnaire. This questionnaire was particularly aimed at gathering the students’ views on (1) the importance of English language in students’ studies and future careers, (2) basic skills needed in the nursing English course and the students’ problems, and (3) suggestions for the development of English language curriculum. In addition to the questionnaire, semi-structured interviews with 12 students were also carried out to gather their perspectives related to the study. The collected data were descriptively analyzed and presented in the form of frequency and procentage. The results revealed that English was perceived as very important for students both in their academic studies and future careers. The students wanted basic English language skills to be included and emphasized in the course for a number of reasons, naming speaking as the most important skill to master. Limited vocabulary and poor grammar were two most highly rated problems the students perceived in their study. The students desired to have a combination of general English and specific nursing English throughout the study. Keywords: ESP needs, English for nursing, needs analysis, nursing students